2010
DOI: 10.1371/journal.pone.0012706
|View full text |Cite
|
Sign up to set email alerts
|

MPF Governs the Assembly and Contraction of Actomyosin Rings by Activating RhoA and MAPK during Chemical-Induced Cytokinesis of Goat Oocytes

Abstract: The interplay between maturation-promoting factor (MPF), mitogen-activated protein kinase (MAPK) and Rho GTPase during actin-myosin interactions has yet to be determined. The mechanism by which microtubule disrupters induce the formation of ooplasmic protrusion during chemical-assisted enucleation of mammalian oocytes is unknown. Moreover, a suitable model is urgently needed for the study of cytokinesis. We have established a model of chemical-induced cytokinesis and have studied the signaling events leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…In somatic cells, physical and psychological stressors causes oxidative damage by inducing an imbalance between the prooxidant and antioxidant status [67,68] and oxidative stressinduced proteolysis of the anaphase inhibitor securin and mitotic cyclins [62]. Furthermore, studies in rodent [69][70][71] and goat [72,73] oocytes suggest that maturation-promoting factor (MPF) might be an upstream regulator of the MAPK/ MOS pathway during meiotic maturation. It is thus suggested that maternal restraint induces intraoocyte oxidative stress, which then reduces MAPK activities (Fig.…”
Section: Stress and Oocyte Aneuploidymentioning
confidence: 99%
“…In somatic cells, physical and psychological stressors causes oxidative damage by inducing an imbalance between the prooxidant and antioxidant status [67,68] and oxidative stressinduced proteolysis of the anaphase inhibitor securin and mitotic cyclins [62]. Furthermore, studies in rodent [69][70][71] and goat [72,73] oocytes suggest that maturation-promoting factor (MPF) might be an upstream regulator of the MAPK/ MOS pathway during meiotic maturation. It is thus suggested that maternal restraint induces intraoocyte oxidative stress, which then reduces MAPK activities (Fig.…”
Section: Stress and Oocyte Aneuploidymentioning
confidence: 99%
“…Our previous study using goat oocytes indicated that demecolcine induced ooplasmic protrusion by increasing maturation promoting factor (MPF) and mitogen activated protein kinase (MAPK) activities via activating MAD2 (Wu et al, 2010). Both caffeine and MG132 are MPF-activating agents; whereas MG132, a specific inhibitor of proteasome catalytic activity, activates MPF by preventing cyclin B degradation (Glotzer et al, 1991;Josefsberg et al, 2000), caffeine increases MPF activity by inhibiting Myt1/Wee1 and dephosphorylating CDC2A (Kikuchi et al, 2000;Smythe and Newport, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether adiponectin acts on oocyte maturation through the MEK 1/2 MAPK pathway, COCs ( n = 430 oocytes) were randomly distributed in groups of 20–25 for one of the following treatments: IVM with 0 or 5 μg/ml adiponectin, in the presence or absence of a specific inhibitor of MEK 1/2 (10 μM; U0126, EMD Millipore Corp., Billerica, MA, USA). The U0126 is a highly selective inhibitor of MEK 1/2 activation and the MAPK cascade in granulosa cells and goat oocytes (Coyral‐Castel, Ramé, Fatet, & Dupont, ; Wu et al, ). The nuclear meiotic stage was determined after 27 hr of IVM.…”
Section: Methodsmentioning
confidence: 99%